A sociolinguistic study of Bikol verbal folklore adviser, Vivencio R. Jose. - Realubit, Maria Lilia Fuentebella; Jose, Vivencio R. (1986)
This is a sociolinguistic study of Bikol folklore. Focus is on four folklore genres -- riddles, proverbs, legends, and mythis. The study has adopted a formal and functional framework for the analysis by integrating the linguistic and narrative aspects with a descriptive model and explanatory theory. The role of language in folklore is the central concern, We assume that the linguistic means by which the folkloristic structure is manifested cannot be ignored. This is true in the riddles and proverbs and just as well in the legends and myths. The second focus of attention is the relationship between folklore and social structure, or the situation of context in which the item of text is actualized. The data demonstrate that folkloric situations are grammatically, adequately, and appropriately expressed in language. The communal competetive and dialectical circumstances in which folkloric exchanges were held show their acceptance by the people.
Typescript.
Thesis (Ph.D.)--University of the Philippines, Diliman
Keywords: Folklore -- Philippines -- Bicol region; Folklore -- Structural analysis; Sociolinguistics -- Philippines -- Bicol region